(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The period of life between childhood and adulthood known as adolescence, lasts from the ages of 10 to 19. It is the special time in human development and a crucial moment to establish the groundwork for long term health. Teenagers grow quickly in all areas-physical, cognitive and psychological. The five leading characteristics of adolescence are biological growth and development, an undefined status, increased decision-making, increased pressures, and the search for self. Mental health is the balanced development of an individual’s personality and emotions, an attitude to live in harmony with those around you. when someone is in the condition of good mental health, they are able to acknowledge and embrace their own skills. In this positive sense, mental health is the foundation of personal well-being, and the effective functioning of the community; Interfaith oral care is needed to promote mental health. Academic achievement or achievement (academic) as a result of education – the extent to which a student, teacher, or organization has achieved its educational goals. Academic Success is often measured by ongoing exams or assessments, but there is no general agreement on the best way to test it or which aspect is most important - the process knowledge as skill or claimed knowledge as fact. Academic success can be defined as excellence in all subjects, both in the classroom and in extracurricular activities; including athletic excellence, manners, confidence, communication skills, punctuality, assertiveness, art, culture, etc. Academic success is one of the most comprehensive successes that study the social consequences of mental health problems. Anxiety is a state of unease and concern that is typically unfocused and generalised, representing an overreaction to a circumstance that is only perceived as frightening in the mind. It frequently comes with symptoms like tense muscles, agitation, exhaustion, difficulty breathing, stomach tightness, nausea and difficulty in focus. The objective of this paper is to find impact of anxiety and achievement on mental health of adolescents.